The Effect of Audit Committee, Institutional Ownership, Independent Commissioners, and Sales Growth on Tax Avoidance (Empirical Study of Mining Sector Companies Listed on the Indonesia Stock Exchange in 2017-2022) - Marianto MARIANTO; Suharmadi SUHARMADI (PT Keberlanjutan Strategis Indonesia, 2025)
This study aims to examine and analyze the effect of the audit committee, institutional ownership, independent commissioners, and sales growth on tax avoidance. The object of this research is mining sector companies listed on the Indonesia Stock Exchange (IDX) from 2017 to 2022. The sample in this study was obtained using a non-probability sampling technique, specifically purposive sampling. The study utilized a sample of 17 companies over a 6-year period. The data analysis method used was multiple linear regression analysis with the assistance of IBM SPSS Statistics version 27. The results of this study indicate that the audit committee and institutional ownership have a negative and significant effect on tax avoidance, while independent commissioners and sales growth do not have a significant effect on tax avoidance.